2016
DOI: 10.1093/annonc/mdv592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing in a cohort of young patients with HER2-amplified breast cancer

Abstract: Patients aged <41 at diagnosis with HER2+ breast cancer and no family history of breast cancer can be reassured that they have a low chance of being a high-risk gene carrier. If there is a strong family history, not only BRCA but also TP53 gene testing should be considered. The clinical utility of testing lower penetrance CSGs remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The strategy of adding oxaliplatin weekly to fluoropyrimidine-based chemotherapy was well studied. Except the CAO/ARO/AIO-04 trail, results from randomized phase III trials: STAR-01, ACCORD 12, NASPBR-04, and PETACC-6 showed that adding oxaliplatin to 5-FU/capecitabine-based preoperative CRT increased acute toxicity, but failed to improve the pCR rate and disease free or overall survival 10 - 13 , 17 . The CAO/ARO/AIO-04 trail with more than 1250 patients recruited reported a significant improvement of pCR rate (13% vs. 17%, P=0.04) and 3-years DFS (71.2% vs. 75.9%, P=0.03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of adding oxaliplatin weekly to fluoropyrimidine-based chemotherapy was well studied. Except the CAO/ARO/AIO-04 trail, results from randomized phase III trials: STAR-01, ACCORD 12, NASPBR-04, and PETACC-6 showed that adding oxaliplatin to 5-FU/capecitabine-based preoperative CRT increased acute toxicity, but failed to improve the pCR rate and disease free or overall survival 10 - 13 , 17 . The CAO/ARO/AIO-04 trail with more than 1250 patients recruited reported a significant improvement of pCR rate (13% vs. 17%, P=0.04) and 3-years DFS (71.2% vs. 75.9%, P=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several large randomized phases III trials tested the efficacy of adding oxaliplatin to the multimodal neoadjuvant treatment for LARC. However, except the German CAO/ARO/AIO-04 study showing an improved disease free survival, integrating oxaliplatin into the combined modality strategies failed to show a survival benefit 10 - 13 . As a result, the strategy of simply adding oxaliplatin concomitant to conventional CRT remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Eccles et al [39] also classified patients for TP53 screening taking into consideration HER2 status (score 3 +) from a large UK cohort study. Using this approach, 3% (9/304) of women were diagnosed with HER2-amplified BC ≤ 40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of HER2 has been reported as more common in women who carry a TP53 pathogenic variant compared with the population as a whole (Melhem-Bertrandt et al, 2012). In studies of patients with HER2+ breast tumors in the absence of LFS criteria, the TP53 frequency was higher, reported as 7.0% for women diagnosed before 31 years (Eccles et al, 2016), but only 0.5% when women were diagnosed before the age of 50 years (Rath et al, 2013).…”
Section: Tp53-targeted Studies: Frequency Of Tp53 Carriers In Nonconvmentioning
confidence: 99%